Bintang Pandu Driving Institute Sdn. Bhd / Wan Mohd Yusrizal Wan Hanapi ... [et al.] - Wan Hanapi, Wan Mohd Yusrizal; Naim Ibrahim, Mohd Badrul; Mohd Noor, Mohd Rohafizan; Abd Rahim, Zul Ilham (2002)
Looking at today's situation, there are a lot of people especially the students want to take a driving license. This is because many cases from police department say that majority of students don not have a driving license especially a motor biker. So, we make a decision to train people that want to take a driving license. Besides that, we realize only a few driving institution that active especially in Perlis. So, we as a partnership in Bintang Pandu Driving Institute Sdn. Bhd agreed to start business on 1 January 2004 suitable with current especially people who live in town or village that hope they can take a driving license with cheap and fast operation Bintang Pandu Driving Institute Sdn Bhd is a strategic place. This is because all the factors such as school, high learning institution and government department situated here. It is also located in residences area, so it easy to people especially students to go, in our driving institution. We hope that our driving institution will succeed and excel in future as ones of the biggest and largest driving institution among all the competitors.